What drives milex in Zimbabwe? A comparative study: Paper presented at ‘The Fourteenth Annual International Conference on Economics and Security at Izmir University of Economics, Turkey, on June 17-18, 2010. - Tambudzai, Zachary; Harris, Geoff (Midlands State University, 2016)
Most of the papers on the determinants of milex in Africa have taken a quantitative or econometric approach. Few have attempted a qualitative approach that investigates underlying motives for huge milex especially in Southern Africa. This study tests a model located within the public choice approach to economics using data drawn from interviews with key informants and documentary sources to derive salient determinants of milex in Zimbabwe and South Africa. The empirical findings suggest that Zimbabwe’s milex since 1980 has been influenced by internal political dynamics and to a lesser extend by economic factors. The most significant factors include regime security, elite corruption and liberation war hang-over and fear. In South Africa the milex level and composition are clearly formulated, transparent and are adhered to with respect to recurrent expenditures. However, recent military procurement history reveals increasing cabinet authoritarianism, a lack of transparency, significant opportunities for corruption and, arguably, inappropriate decisions.